The C-terminal of rat 4-hydroxyphenylpyruvate dioxygenase is indispensable for enzyme activity - Lee, M; Zhang, Z; MacKinnon, C; Baldwin, J; Crouch, N (Elsevier, 1996)
We have cloned and overexpressed rat 4-hydroxyphenylpyruvate dioxygenase (4HPPD) in Escherichia coli. The soluble, active recombinant enzyme was shown to contain both 4HPPD and α-ketoisocaproate dioxygenase (αKICD) activity. However, upon truncation of the 14 amino acids at the C-terminus by site-directed mutagenesis, the resulting mutant enzyme (rat F antigen) exhibited complete loss of 4HPPD and αKICD activities. This finding suggests that the C-terminal extension domain plays an essential role in the catalytic activity of the enzyme.